Specifications for public library - Beighle, E. E. (My University, 1908)
Introduction: Specifications of material and workmanship required, and to be furnished, for the erection and completion of a Public Library for the City of [blank] in accordance with drawings and this specification of Architect E. E. Beighle, and under the supervision of a competent Structural Engineer to be appointed by the Building Committee of the City Council.
Citation: Beighle, E. E. Specifications for public library. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Architecture; Blueprints; Libraries; Engineering; Graduating theses; Senior theses; Theses